2017
DOI: 10.1371/journal.pone.0182969
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of noninvasive liver fibrosis indexes in predicting portal hypertension in patients with cirrhosis

Abstract: BackgroundRecent data suggest that noninvasive liver fibrosis indexes could be useful for predicting esophageal varices (EV) in cirrhotic patients. However, thus far, the diagnostic efficacy of these indexes in predicting portal hypertension (PH) in cirrhotic patients has been poorly evaluated.AimsTo evaluate the diagnostic efficacy of noninvasive liver fibrosis indexes in the diagnosis of PH.MethodsA total of 238 cirrhotic patients underwent hepatic venous pressure gradient (HVPG) evaluation and relevant seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
3
23
1
Order By: Relevance
“…But they concluded that since all studied indices had AUC<0.8, they could not be considered as accurate indices for prediction of portal hypertension. 7 In line with these results, we also showed that all indices had AUC ≤0.8 except the FORNS index. This may be due to this fact that all these indices were initially developed for the prediction of liver fibrosis in cirrhotic patients with hepatitis C. 12 However, we included cirrhotic patients with various etiology in the present study, intending to compare the mean score of different indices in patients with different etiology and disease severity.…”
Section: Discussionsupporting
confidence: 85%
“…But they concluded that since all studied indices had AUC<0.8, they could not be considered as accurate indices for prediction of portal hypertension. 7 In line with these results, we also showed that all indices had AUC ≤0.8 except the FORNS index. This may be due to this fact that all these indices were initially developed for the prediction of liver fibrosis in cirrhotic patients with hepatitis C. 12 However, we included cirrhotic patients with various etiology in the present study, intending to compare the mean score of different indices in patients with different etiology and disease severity.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies investigated the use of simple liver fibrosis scores based on indirect liver fibrosis markers, such as fibrosis-4 (FIB-4), AST to platelet ratio Index (APRI), or Lok [79][80][81][82][83] as surrogates of portal hypertension. As expected, these markers showed some correlation with HVPG, in particular, if non-ACLD patients were included; however, none of these markers is sufficiently accurate to be of clinical value beyond the diagnosis of advanced liver fibrosis (i.e., ruling-out or ruling-in ACLD).…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…Similar liver stiffness cutoffs have been shown to predict clinically significant varices among patients with BA with normalized bilirubin . In addition, similar liver stiffness and APRI values correlate with PH defined by hepatic venous pressure gradient measurement, supporting the application of these cut‐off values into clinical practice . Overall, APRI was the best predictor of PH.…”
Section: Discussionmentioning
confidence: 52%